DOES THE CHARACTER OF HYPERTENSION AND MODE OF THERAPY DETERMINE CHANGES IN THE QUALITY OF LIFE? - Cegła, Bernadeta; Filanowicz, Małgorzata; Dowbór-Dzwonka, Aneta; Szynkiewicz, Ewa (Medical and Biological Sciences, 2012)
Introduction. The study of factors which determine changes of life quality in patients with arterial hypertension is crucial to relevancy and effectiveness of secondary activities which are implemented for patients' care. Does the character of hypertension and mode of therapy determine changes in the quality of life? For many years, the improvement in quality of life has been taken into account. Apart from activities eliminating the symptoms of disease and prolonging the duration of patient's life, it is essential to improve the quality of life. Conducting research aiming at determining factors allows taking proper preventive and reparative steps. The aim of the study is to determine: - what the level of quality of life in patients with arterial hypertension is, - if duration of illness influences changes in the quality of life, - if differences in quality of life reflect severity of hypertension, - if the type of leading symptom and its intensity change the quality of life. Materials and methods. The studied group comprised of 185 patients with arterial hypertension. The mean age of patients was 55.6±14.2 years. Diagnostics survey was applied as the analysis method. The self-developed ‘Quality of Life Questionnaire’ and ‘Interview Questionnaire’ were exploited. The study was performed in the area of city of Bydgoszcz. The results showed that mean Quality of Life [QoL] in patients was 0.58, where 0 represented the lowest and 1.0 the highest level of QoL. The lowest level of QoL (0.54) was demonstrated by patients with long history of hypertension. In patients with short duration of disease the Quality of Life was 0.69. The level of hypertension had the most important influence on the Quality of Life. The dependence between the leading symptom and the quality of life was not demonstrated. The level of intensity of the leading symptom of the disease revealed to be the most strongly influencing factor. Conclusions. 1. The quality of life in patients with arterial hypertension is significantly low. 2. The duration of the disease influences the patients' quality of life. 3. The mode of therapy is not a relevant factor causing changes of life quality. 4. The intensity of the leading symptom determines the quality of life in patients.